Narrowband Blue and Red LED Supplements Impact Key Flavor Volatiles in Hydroponically Grown Basil Across Growing Seasons - Hammock, Hunter A.; Kopsell, Dean A.; Sams, Carl E. (Frontiers in Plant Science, 2021)
The use of light-emitting diodes (LEDs) in commercial greenhouse production is rapidly increasing because of technological advancements, increased spectral control, and improved energy efficiency. Research is needed to determine the value and efficacy of LEDs in comparison to traditional lighting systems. The objective of this study was to establish the impact of narrowband blue (B) and red (R) LED lighting ratios on flavor volatiles in hydroponic basil (Ocimum basilicum var. “Genovese”) in comparison to a non-supplemented natural light (NL) control and traditional high-pressure sodium (HPS) lighting. “Genovese” basil was chosen because of its high market value and demand among professional chefs. Emphasis was placed on investigating concentrations of important flavor volatiles in response to specific ratios of narrowband B/R LED supplemental lighting (SL) and growing season. A total of eight treatments were used: one non-supplemented NL control, one HPS treatment, and six LED treatments (peaked at 447 nm/627 nm, ±20 nm) with progressive B/R ratios (10B/90R, 20B/80R, 30B/70R, 40B/60R, 50B/50R, and 60B/40R). Each SL treatment provided 8.64 mol ⋅ m−2 ⋅ d–1 (100 μmol ⋅ m–2 ⋅ s–1, 24 h ⋅ d–1). The daily light integral (DLI) of the NL control averaged 9.5 mol ⋅ m−2 ⋅ d–1 during the growth period (ranging from 4 to 18 mol ⋅ m−2 ⋅ d–1). Relative humidity averaged 50%, with day/night temperatures averaging 27.4°C/21.8°C, respectively. Basil plants were harvested 45 days after seeding, and volatile organic compound profiles were obtained by gas chromatography–mass spectrometry. Total terpenoid concentrations were dramatically increased during winter months under LED treatments, but still showed significant impacts during seasons with sufficient DLI and spectral quality. Many key flavor volatile concentrations varied significantly among lighting treatments and growing season. However, the concentrations of some compounds, such as methyl eugenol, were three to four times higher in the control and decreased significantly for basil grown under SL treatments. Maximum concentrations for each compound varied among lighting treatments, but most monoterpenes and diterpenes evaluated were highest under 20B/80R to 50B/50R. This study shows that supplemental narrowband light treatments from LED sources may be used to manipulate secondary metabolic resource allocation. The application of narrowband LED SL has great potential for improving overall flavor quality of basil and other high-value specialty herbs.